I'm gonna wreck it, again: the false dichotomy of "healthy" and "toxic" masculinity in Ralph Breaks the Internet. Issue 4 (8th August 2022) - Dosser, Max
ABSTRACT: This article examines the representation of masculinity in the animated Disney film Ralph Breaks the Internet (2018). Popular reviews of the film focused heavily on critiques of toxic masculinity. Often associated with homophobic and misogynistic speech, the concept of toxic masculinity ultimately serves to reinforce and rescue elements of hegemonic masculinity by painting "toxic" male behaviors as something that can be "cured" or "fixed." To probe the troubled concept of toxic masculinity as seen in animated media, this article demonstrates how Ralph Breaks the Internet reifies a false dichotomy of healthy and toxic masculinity. Through examining the ways Ralph's physical appearance, his behaviors, his manipulative relationships with women, and the film's ultimate resolution reflect the current crisis of masculinity, this article argues that while reviews claim the film critiques toxic masculinity, the film itself actually reinscribes qualities of hegemonic masculinity. By invoking toxic masculinity in scholarship and reviews, critics obscure other critiques of masculinity films may put forward—positive and negative.